2016
DOI: 10.18632/oncotarget.10644
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic effect of liver metastasis in lung cancer patients with distant metastasis

Abstract: Because the need of clinical prognostic evaluation by specific metastatic organ, we aim to analyze the prognostic factors in lung cancer patients with M1b disease with Surveillance Epidemiology and End-Results database (SEER). This retrospective study evaluated lung cancer patients of adenocarcinoma (AD), squamous cell carcinoma (SQCC), and small cell lung cancer (SCLC) selected from SEER. We provided the prognostic correlates of overall survival (OS) and lung cancer-specific survival (LCSS) in this population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
107
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 135 publications
(122 citation statements)
references
References 22 publications
(28 reference statements)
13
107
2
Order By: Relevance
“…Our results suggest that liver metastasis is the most influential and statistically significant covariate for tumor growth. This finding is consistent with recent reports showing that liver metastasis is associated with poor prognosis in various cancers . We also showed that baseline tumor size and IC are the most influential and significant covariates for tumor killing after durvalumab treatment.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results suggest that liver metastasis is the most influential and statistically significant covariate for tumor growth. This finding is consistent with recent reports showing that liver metastasis is associated with poor prognosis in various cancers . We also showed that baseline tumor size and IC are the most influential and significant covariates for tumor killing after durvalumab treatment.…”
Section: Discussionsupporting
confidence: 93%
“…This finding is consistent with recent reports showing that liver metastasis is associated with poor prognosis in various cancers. [13][14][15][16][17] We also Figure 2 Forest plots of covariate effects on k g (a) and k kill (b) estimated from the full covariate tumor kinetic model and survival hazard (c) from the full covariate survival model. Circles represent the calculated percent change in the parameter value from the reference value at the indicated covariate values, using the point estimates of the respective covariate effects; error bars represent the 95% confidence intervals of the covariate effects based on the relative standard error estimates from NONMEM; dashed vertical lines represent the reference value; dotted lines represent the 30% change from reference value.…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast to lung cancer where prognostic differences have been found according to this parameter[12,13]. …”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, data indicating a poor response in patients with liver tumors could be confounded with the aggressive nature of tumors that metastasise to the liver. Some evidence indicates that patients with liver metastases have more metastases in other sites indicating a potentially more advanced stage in the cohort of patients with liver metastases …”
Section: Discussionmentioning
confidence: 99%
“…Some evidence indicates that patients with liver metastases have more metastases in other sites indicating a potentially more advanced stage in the cohort of patients with liver metastases. 24,58 While the injection of genetically identical tumor lines enabled the specific influence of the tissue of tumor growth to be assessed in our mouse models, it should be acknowledged that differences to the human setting need to be considered when drawing parallels to the clinic. In human cancers, the genetics of tumors in distal sites compared with the primary location, and even within the primary tumor, can be highly heterogeneous.…”
Section: Discussionmentioning
confidence: 99%